1805. Impact of Antimicrobial Stewardship Interventions Using Rapid Molecular Testing on the Appropriate Use of Antiviral Therapy and Reduction of Unnecessary Antibiotic Therapy for Patients Admitted With Acute Influenza. (26th November 2018) - Politis, Paula; Tan, Michael J; Kallstrom, George; File, Thomas
Abstract: Background: Rapid molecular tests combined with Antimicrobial Stewardship Program (ASP) interventions have provided opportunities to optimize patient outcomes and reduce unnecessary antimicrobial use. Our institution currently uses an FDA approved influenza/respiratory syncytial virus polymerase chain reaction (PCR) assay and multiplex respiratory panel. In addition, our institution commonly utilizes procalcitonin (PCT) levels. The ASP at Summa Health System – Akron Campus (SHS-AC) routinely recommends use of these rapid diagnostic tests to assist with antimicrobial and antiviral usage, including the discontinuation of antibiotics in influenza positive patients in the absence of a concurrent bacterial infection. Methods: A retrospective review of all ASP interventions on influenza positive patients at SHS-AC was performed from December 2017 to March 2018. The ASP reviewed all patients on broad-spectrum antibiotics >48 hours and all influenza positive patients without Infectious Disease consultation. The appropriateness of antimicrobial and antiviral therapy was assessed, including assessment of culture and PCR results, PCT levels, indication of therapy, and renal function. For patients with a positive influenza PCR and low PCT without evidence of bacterial infection, the recommendation was to discontinue antibacterial use. Data collected included: intervention type, acceptance rate, PCT levels, and influenza subtype. Results: Two hundred thirty-three total recommendations were made by the ASP on influenza positive patients, with a 96.6% acceptance rate. Interventions included the following: obtain PCT level (54/233), de-escalate or stop antibiotics based on culture, PCR, and PCT results (116/233), obtain influenza or respiratory PCR (8/233), initiate oseltamivir (37/233), and other (18/233). Conclusion: ASP intervention combined with PCT levels and PCR results contributed to the reduction of unnecessary antibiotic use, and the initiation of oseltamivir therapy in influenza-positive patients. Disclosures: T. File, BioMerieux: Scientific Advisor, Consulting fee. Curetis: Scientific Advisor, Consulting fee. Melinta: Scientific Advisor, Consulting fee. Merck: Scientific Advisor, Consulting fee. MotifBio: Scientific Advisor, Consulting fee. Nabriva: Investigator and Scientific Advisor, Consulting fee and Research grant. Pfizer: Scientific Advisor, Consulting fee. Paratek: Scientific Advisor, Consulting fee.